2004
DOI: 10.1103/physrevc.69.044603
|View full text |Cite
|
Sign up to set email alerts
|

One-neutron removal reactions on light neutron-rich nuclei

Abstract: A study of high energy (43--68 MeV/nucleon) one-neutron removal reactions on a range of neutron-rich psd-shell nuclei (Z = 5--9, A = 12--25) has been undertaken. The inclusive longitudinal and transverse momentum distributions for the core fragments, together with the cross sections have been measured for breakup on a carbon target. Momentum distributions for reactions on tantalum were also measured for a subset of nuclei. An extended version of the Glauber model incorporating second order noneikonal correctio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
118
2
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 102 publications
(199 reference statements)
13
118
2
1
Order By: Relevance
“…It has been experimentally shown that none of the odd mass neutron-rich carbon isotopes, GS assignment was performed through the study of GS properties based on the direct reaction [3][4][5][6][7], β-delayed neutron spectroscopy of the β decay of 17 C [8], and magnetic moment of 17 C [9]. In the extremely neutron-rich nucleus 19 C with N = 13, the I π GS value again becomes 1/2 + ; this was confirmed and discussed in connection with the formation of a neutron halo [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been experimentally shown that none of the odd mass neutron-rich carbon isotopes, GS assignment was performed through the study of GS properties based on the direct reaction [3][4][5][6][7], β-delayed neutron spectroscopy of the β decay of 17 C [8], and magnetic moment of 17 C [9]. In the extremely neutron-rich nucleus 19 C with N = 13, the I π GS value again becomes 1/2 + ; this was confirmed and discussed in connection with the formation of a neutron halo [6,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…(1) 88 (2) 67 (1) 295 (2) 352 (1) 511 (2) 596 (5) 609 (2) 696 (8) 770 (2) 936 (2) 1123 (3) 1242 (3) 1411 (5) 4782 ( …”
unclassified
“…From these, it is expected that the states arising from a coupling of the p 1/2 proton hole to the 2 + , 4 + states of the 20 O core are mostly excited [7]. The ground state spin of 19,21 N was determined to be 1/2 − and that of 20 N to be 2 − [8]. No experimental data are available for the excited states of nitrogen nuclei heavier than A = 19.…”
Section: Introductionmentioning
confidence: 99%
“…Fast one-and two-neutron removal reactions from the neutron-rich carbon isotopes have been studied experimentally by several authors [8][9][10][11][12][13][14][15] 19 C (lower part). The energy intervals for transitions applicable to the inclusive cross sections for the indirect two-neutron removal (one-neutron removal followed by neutron emission), σ −1n(e) , and direct two-neutron removal, σ −2n(d) , reaction mechanisms are shown.…”
Section: Knockout Reaction Analysesmentioning
confidence: 99%